Telomere length is associated with HIV infection, methamphetamine use, inflammation, and comorbid disease risk. (1st April 2021) - Mehta, Sanjay R.; Iudicello, Jennifer E.; Lin, Jue; Ellis, Ronald J.; Morgan, Erin; Okwuegbuna, Oluwakemi; Cookson, Debra; Karris, Maile; Saloner, Rowan; Heaton, Robert; Grant, Igor; Letendre, Scott; et al.
Highlights: Leukocyte telomere length (LTL) is associated with aging-related outcomes. HIV and METH dependence independently and adversely affect LTL. LTL may estimate the risk of aging related comorbidities in PWH +/- METH dependence. LTL may also help identify individuals at risk for neurocognitive decline. Abstract: Background: HIV infection and methamphetamine dependence (METH) are each associated with inflammation and premature aging, but their impact on biological aging is difficult to measure. Here we examined the impact of HIV and METH on leukocyte telomere lengths (LTL), and the correlations between LTL and other aging biomarkers. Methods: The study was a cross-sectional analysis of 161 individuals categorized by HIV and methamphetamine (METH) dependence status into four groups: HIV-METH- (n = 50), HIV-METH+ (n = 29), HIV + METH- (n = 40), and HIV + METH+ (n = 42). We analyzed the relationships of leukocyte telomere length (telomere to single copy gene [T/S] ratio) with demographic and clinical data as well as a panel of biomarkers of inflammation and endothelial activation measured in blood and cerebrospinal fluid (CSF). Results: HIV and METH were independently associated with shorter T/S ratio, even after adjusting for demographics and leukocyte count (R 2 = 0·59, p < 0·0001). Higher plasma C-reactive protein (p = 0·0036) and CSF VCAM-1 (p = 0·0080) were also associated with shorter T/S ratio. A shorter T/S ratio was associated with higher risk for cardiovascular disease (p < 0·0001) and stroke (p < 0·0001), worse motor functioning (p = 0·037) and processing speed (p = 0·023), more depressive symptoms (p = 0·013), and higher CSF neurofilament-light (p = 0·003). Conclusions: HIV and METH dependence were each associated with shorter telomeres. After adjusting for demographics, HIV, and METH, T/S ratio remained associated with aging-related outcomes including neurocognitive impairment, neurodegeneration, risks of cardiovascular disease and stroke. While not establishing causality, this study supports using the T/S ratio as a biomarker for estimating the impact of HIV and comorbidities on long-term health.